2009
DOI: 10.3168/jds.2008-1722
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH and level of concentrate in the diet on the production of biohydrogenation intermediates in a dual-flow continuous culture

Abstract: Milk fat depression in cows fed high-grain diets has been related to an increase in the concentration of trans-10 C 18:1 and trans-10,cis-12 conjugated linoleic acid (CLA) in milk. These fatty acids (FA) are produced as a result of the alteration in rumen biohydrogenation of dietary unsaturated FA. Because a reduction in ruminal pH is usually observed when high-concentrate diets are fed, the main cause that determines the alteration in the biohydrogenation pathways is not clear. The effect of pH (6.4 vs. 5.6) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
78
1
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 44 publications
(55 reference statements)
9
78
1
7
Order By: Relevance
“…Importantly, shifts in ruminal bacteria and BH intermediates (i.e. elevations in the concentration of milk trans10-18:1 at the expense of trans11-18:1) are caused by low ruminal pH (Qiu et al, 2004;Fuentes et al, 2009), or by a direct toxic effect of PUFA on bacteria (Bauman and Griinari, 2001;Maia et al, 2007). In agreement with previous studies (Chilliard et al, 2009;Mohammed et al, 2011), trans10-18:1 was negatively associated with CH 4 in the present study, whereas trans11-18:1 was not correlated (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, shifts in ruminal bacteria and BH intermediates (i.e. elevations in the concentration of milk trans10-18:1 at the expense of trans11-18:1) are caused by low ruminal pH (Qiu et al, 2004;Fuentes et al, 2009), or by a direct toxic effect of PUFA on bacteria (Bauman and Griinari, 2001;Maia et al, 2007). In agreement with previous studies (Chilliard et al, 2009;Mohammed et al, 2011), trans10-18:1 was negatively associated with CH 4 in the present study, whereas trans11-18:1 was not correlated (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…In this study the trans-10 isomers were associated with a decline in milk fat (%) from 3.89 to 3.25 (Steele et al, 2012). During acidosis, these FA are a result of intermediates from a secondary biohydrogenation pathway of C18:2 n-6 (Fuentes et al, 2009). An increase in ruminally derived trans-10 isomer is closely linked with milk fat depression, (Bauman and Griinari, 2003).…”
Section: Resultsmentioning
confidence: 62%
“…Baumgard et al (2000) detected a relationship in milk fat depression and increases in trans-10 cis-12 and C18:1 trans-10. In addition Fuentes et al (2009), also demonstrated that a pH of 5.6 decreased the trans-11 C18:1 and cis-9, trans-11 CLA; and increased the concentration of trans-10 C18:1, trans-10 cis 15 C18:2 and trans-10, cis-12 CLA. These studies indicate that the biohydrogenation intermediated FA in milk could be indicators the presence of SARA, as they are closely linked to rumen pH.…”
Section: Resultsmentioning
confidence: 77%
“…Both the composition and amount of concentrates in the diet influences the extent of lipolysis and BH in the rumen (Palmquist et al, 2005). At least part of the influence of higher concentrate supplementation on ruminal lipid metabolism is thought to be mediated via decreases in rumen pH (Fuentes et al, 2009) and alterations in microbial communities (Weimer et al, 2010). In the present investigation, increases in the F : C ratio of diets containing SFO resulted in higher milk fat 4:0 to 12:0 concentrations, without altering milk 14:0 and 16:0 content.…”
Section: Discussionmentioning
confidence: 99%